False Blister Beetles, (Insecta: Coleoptera: Oedemeridae) - Ross H. Arnett, Jr. (EDIS, 2003)
"False blister beetles," sometimes known also as "pollen feeding beetles," are unique in that adults of all the approximately 1,000 species in the world are obligate pollen feeders. They obtain their common name because many species cause blisters when pinched or squashed against the skin. Being pollen feeders, they are often common on flowers. They are also attracted to lights, and their numbers can be vast at night, especially on the Florida Keys. Oxycopis mcdonaldi (Arnett) causes skin blistering and makes itself a nuisance at resort areas where the beetles are attracted by night lights around swimming pools, tennis courts, and open air restaurants. Yet another species, Nacerdes melanura (L.), the "wharf borer," is common around wood pilings where its larvae bore into and weaken the wood of docks and adjacent buildings. This document is EENY-154 (originally published as DPI Entomology Circular 259), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000.